Application of Make a Match Model to Improve Learning Outcomes of Knowing Malaikat on PAI Subject - Moch. Kusnun Nadhir; Fanani, Moh. Zainal; Khasbulloh, Muhammad Nabil; Marwan, Iwan (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This research aims to determine the implementation of the Make A Match Model to improve Learning Outcomes of Knowing Malaikat on PAI subject. with the research subjects being class IV students at SDN 1 Berbek. The results showed that there is an increase in student learning outcomes through the Make a Match method. The results of observations during the action increased in each cycle. In cycle I, it was discovered that 62.5% of the students who participated in the Make a Match method reached 62.5% and had not yet achieved completion. Furthermore, in cycle II there was a drastic increase, namely 87.5%.